Molecular mechanisms and targeted therapy of progranulin in metabolic diseases - Wang, Xiaxia; Liang, Yonglin; Yang, Fan; Shi, Yangyang; Shao, Ruiwen; Jing, Ruge; Yang, Tong; Chu, Qiao; An, Dong; Zhou, Qi; Song, Jiayi; Chen, Haolan; et al. (Frontiers in Endocrinology, 2025)
Progranulin (PGRN) is a secreted glycoprotein with cytokine-like properties, exerting tripartite mechanisms of inflammation suppression, tissue repair promotion, and metabolic regulation. This multifaceted functionality positions PGRN as a potential “multi-effect therapeutic strategy” for metabolic disorders characterised by cartilage degradation and imbalanced bone remodelling, potentially establishing it as a novel therapeutic target for such conditions. Osteoarthritis, rheumatoid arthritis, intervertebral disc degeneration, osteoporosis, periodontitis, and diabetes-related complications—representing the most prevalent metabolic diseases—currently lack effective treatments due to incomplete understanding of their precise pathogenic mechanisms. Recent studies have revealed that PGRN expression levels are closely associated with the onset and progression of these metabolic disorders. However, the exact regulatory role of PGRN in these diseases remains elusive, partly owing to its tissue-specific actions and context-dependent dual roles (anti-inflammatory vs. pro-inflammatory). In this review, we summarise the structure and functions of PGRN, explore its involvement in neurological disorders, immune-inflammatory diseases, and metabolic conditions, and specifically focus on its molecular mechanisms in metabolic diseases. Furthermore, we consolidate advances in targeting PGRN and the application of its engineered derivative, Atsttrin, in metabolic bone disorders. We also discuss potential unexplored mechanisms through which PGRN may exert influence within this field or other therapeutic domains. Collectively, this work aims to provide a new framework for elucidating PGRN’s role in disease pathogenesis and advancing strategies for the prevention and treatment of metabolic disorders.